Elevated sortilin expression discriminates functional from non-functional neuroendocrine tumors and enables therapeutic targeting - Bolduan, Felix; Wetzel, Alexandra; Giesecke, Yvonne; Eichhorn, Ines; Alenina, Natalia; Bader, Michael; Willnow, Thomas E.; Wiedenmann, Bertram; Sigal, Michael (Frontiers in Endocrinology, 2024)
A subset of neuroendocrine tumors (NETs) can cause an excessive secretion of hormones, neuropeptides, and biogenic amines into the bloodstream. These so-called functional NETs evoke a hormone-related disease and lead to several different syndromes, depending on the factors released. One of the most common functional syndromes, carcinoid syndrome, is characterized mainly by over-secretion of serotonin. However, what distinguishes functional from non-functional tumors on a molecular level remains unknown. Here, we demonstrate that the expression of sortilin, a widely expressed transmembrane receptor involved in intracellular protein sorting, is significantly increased in functional compared to non-functional NETs and thus can be used as a biomarker for functional NETs. Furthermore, using a cell line model of functional NETs, as well as organoids, we demonstrate that inhibition of sortilin reduces cellular serotonin concentrations and may therefore serve as a novel therapeutic target to treat patients with carcinoid syndrome.